2010
DOI: 10.1134/s0021364010140043
|View full text |Cite
|
Sign up to set email alerts
|

Weak solution for the Hele-Shaw problem: Viscous shocks and singularities

Abstract: In Hele-Shaw flows a boundary of a viscous fluid develops unstable fingering patterns. At vanishing surface tension, fingers evolve to cusp-like singularities preventing a smooth flow. We show that the Hele-Shaw problem admits a weak solution where a singularity triggers viscous shocks. Shocks form a growing, branching tree of a line distribution of vorticity where pressure has a finite discontinuity. A condition that the flow remains curl-free at a macroscale uniquely determines the shock graph structure. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A main feature of the supercritical regime is the appearance of one-dimensional arcs (we call them whiskers) that point out of the droplet. In the context of [22] these whiskers are interpreted as pressure shock waves. Appearance of the whiskers in the supercritical regime was also observed in [4] (for complex orthogonal polynomials with some exponential weight).…”
Section: Introductionmentioning
confidence: 99%
“…A main feature of the supercritical regime is the appearance of one-dimensional arcs (we call them whiskers) that point out of the droplet. In the context of [22] these whiskers are interpreted as pressure shock waves. Appearance of the whiskers in the supercritical regime was also observed in [4] (for complex orthogonal polynomials with some exponential weight).…”
Section: Introductionmentioning
confidence: 99%
“…However, such an equation can lead to the appearance of final time singularities. To prevent these singularities and to regularize the problem, a term containing the surface tension is usually introduced into the equation describing Laplacian growth (indeed, the other methods for regularization exist, for example, in the combustion problem, the effect of diffusion as a perturbation might be considered [9], in comressible fluid, a singular cusp-like finger triggers shockslines of discontinuity for pressure [35,36]). Unfortunately, in the presence of such a surface tension term, obtaining an analytical solution in the form of poles becomes impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the Whitham equations can be interpreted as the evolution of Riemann surfaces ‡ In Refrs. [1,2] we described hydrodynamics of shocks initiated by the most generic cusp singularity, referred to as a (2,3)-cusp. In local Cartesian coordinates aligned with a cusp axis, the shape of a critical finger is y 2 ∼ x 3 , as in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…
In Hele-Shaw flows at vanishing surface tension, the boundary of a viscous fluid develops cusp-like singularities. In recent papers [1,2] we have showed that singularities trigger viscous shocks propagating through the viscous fluid. Here we show that the weak solution of the Hele-Shaw problem describing viscous shocks is equivalent to a semiclassical approximation of a special real solution of the Painlevé I equation.
…”
mentioning
confidence: 99%
See 1 more Smart Citation